Knowledge, Attitudes, and Behavior of Pregnant Women about HIV Screening - Siswi Wulandari; Erike Yunicha Viridula; Anik Wijayanti; Dyansah Anggraini (Universitas STRADA Indonesia, 2022)
Background: HIV infection is classified as a factor that can affect the death of mother and child. This study aims to find out the knowledge, attitudes, and behavior of pregnant women in conducting HIV tests. Method: this research is quantitative research with a cross-sectional research design with incidental sampling techniques. The population that is pregnant women at Arga Husada Hospital, is as many as 150 pregnant women. The analysis was used in univariate analysis and bivariate analysis using chi-square statistical tests. Result: The knowledge variable shows the result that the p-value is 0.397 which means there is no relationship between knowledge and HIV test behavior and the Attitude variable shows a p-value of 0.001 which means that there is a relationship between pregnant women's attitudes towards HIV testing. Conclusion: Knowledge is not related to HIV test behavior and there is a relationship between pregnant women's attitudes towards HIV testing